Hegel, Selbstischkeit, and the experiential self - Matthews, Paul R. (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
In this essay, I offer a corrective to the standard reading of Hegel as a social constructivist when it comes to matters of the self by shifting the focus from the Phenomenology to his ‘Philosophy of Spirit’ and ‘Anthropology.’ There, a kind-of self or Selbstischkeit is revealed, anticipating the pre-reflective, experiential of the likes of Zahavi and, by extension, Husserl, Sartre, and Merleau-Ponty. I argue that Hegel's conception of the self enhances our understanding of the relationship between the pre-reflective, experiential self and the self of self-consciousness, contributing to the discourse on the continuity between biological and mental life. The self, as it emerges in consciousness, traces its origins to a primarily bodily selfness which is foundational to psychical life. Habit emerges as a vital bridge between this selfness and the self of self-consciousness, offering a dynamic, dialectical framework for thinking the development of the self of self-consciousness in and out of its bodily context.
Keywords: Self; Habit; Consciousness; Organism; Soul